SBSN PBS, dan SUKRI SEBAGAI INSTRUMEN PEMERINTAH DALAM PEMBIAYAAN APBN DAN INVESTASI MASYARAKAT - Suteja Wira Dana Kusuma; Nisa Dely Amalia (Asy-Syari'ah, 2019)
Abstract: The Sharia capital market is currently growing rapidly in the Indonesian economy. One of the instruments, namely sukuk, is being aggressively fulfilling government needs. Sukuk is widely used as a means of financing the APBN for infrastructure development. In addition, sukuk is also used as a means of investment by the community. Sukuk is the safest investment among investors because it is guaranteed by the government.Abstrak: Pasar modal Syariah saat ini sedang berkembang pesat di perekonomi Indonesia. Salah satu instrumennya yaitu sukuk sedang gencar dalam memenuhi kebutuhan pemerintah. Sukuk banyak dijadikan sebagai sarana pembiayaan APBN untuk pembangunan infrastruktur. Selain itu, sukuk juga dijadikan sebagai sarana investasi oleh masyarakat. Sukuk adalah investasi paling aman dikalangan para investor karena dijamin oleh pemerintah.